Negotiated settlements in bribery cases a principled approach - (Abiola) (Edward Elgar Publishing Limited, 2020)
Achieving effective enforcement in cases of complex, multi-layered, multi-jurisdictional acts of bribery that occur in utmost secrecy is a challenging area of corporate crime enforcement. This thought-provoking book examines the scope, benefits and challenges of negotiated settlements - a form of non-trial enforcement - as a mechanism, and demonstrates the need for a more harmonized and principled approach to deterring corporate bribery. Written by a global team of experts with backgrounds in legal practice, policy work and academia, this timely book offers a truly international perspective, considering negotiated settlements in view of a variety of different legal systems and traditions. Drawing on recent empirical research, the contributors' analyses of these settlements in the context of fundamental criminal law principles offer unique insight and functional solutions to the difficult problem of holding corporations liable for crime. - The book's deep reflection on criminal law principles will be beneficial for scholars and students of economic crime, corruption and criminal law. Equally, its contributions to a policy area undergoing rapid development will be invaluable for policymakers, enforcement practitioners and government officials"--